(untitled) (Nordic Journal of African Studies, 1999)
This article starts with a description of an event and its causes, as reported in the Malawi News, Malawi’s leading weekly paper, on March 21st 1998. The event took place at Zomba, the country’s colonial capital. The story is that: two ex-miners, Yusufu Yasini and William Malele, were recently sentenced to seven weeks in jail with hard labour for defying police orders to dismantle roadblocks mounted during a demonstration organized by ex- miners. The demonstration was to show displeasure with the government’s reluctance to pay them their dues [sic: deferred payments, remittances and terminal benefits] for working in South Africa years back.... The amount involved is in the region of K270 million [sic: about US10.8 million]. Similar demonstrations took place in the districts of Mulanje and Nkhota kota [sic: also in Machinga, Mangochi and Salima].